THE CORRELATION BETWEEN EXTROVERT-INTROVERT PERSONALITY TRAIT AND THE FIRST GRADE STUDENTS’ SPEAKING PERFORMANCE AT MAN 3 PEKANBARU - Saefiya, Asmarani; Nuardi, Nuardi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The purpose of this study was to find out the significant correlation between the extrovert-introvert personality trait and their speaking performance at the first grade students of MAN 3 Pekanbaru. This research used quantitative method with correlational research. The target population of this study was the first grade of students at MAN 3 Pekanbaru. The researcher used lottery in doing cluster sampling to choose 1 from 7 classes to be the sample of this research. The sample was class X Science 1 which consisted of 32 students . In this research, for collecting the data the reseacher used questionnaire and test. the researcher distributed the questionnaire to the respondents in order to determine extrovert and introvert students, which consisted of 24 questions developed from indicators of extrovert and introvert and the questions adopted from Eysenck Personality Inventory. Then, the researcher used an oral test to know students’ speaking performance. The reseacher used correlation coefficient of pearson product moment through SPSS 21.0 to analyze the data. Based on the data, the hypotheses Ha was accepted and Ho was rejected. So, it can be concluded thatthere is a Significant Correlation between Extrovert-Introvert Personality Trait and the First Grade Students’ Speaking Perfomance at MAN 3 Pekanbaru.